2015
DOI: 10.1016/j.tics.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding What We See: How We Derive Meaning From Vision

Abstract: Recognising objects goes beyond vision, and requires models that incorporate different aspects of meaning. Most models focus on superordinate categories (e.g., animals, tools) which do not capture the richness of conceptual knowledge. We argue that object recognition must be seen as a dynamic process of transformation from low-level visual input through categorical organisation to specific conceptual representations. Cognitive models based on large normative datasets are well-suited to capture statistical regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
119
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 94 publications
10
119
1
3
Order By: Relevance
“…In Experiment 2, we matched the low-level features between our contexts and objects, and we found that the evidence for context and associative representations disappeared, suggesting that the results from Experiment 1 were influenced by differences in the low-level features that comprised the events. In contrast, we observed evidence for fine-grained object representation in PRC in the absence of a low-level confound, thus corroborating theories that suggest that PRC contains fine-grained semantic representations of objects (e.g., Clarke and Tyler, 2015). …”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In Experiment 2, we matched the low-level features between our contexts and objects, and we found that the evidence for context and associative representations disappeared, suggesting that the results from Experiment 1 were influenced by differences in the low-level features that comprised the events. In contrast, we observed evidence for fine-grained object representation in PRC in the absence of a low-level confound, thus corroborating theories that suggest that PRC contains fine-grained semantic representations of objects (e.g., Clarke and Tyler, 2015). …”
Section: Introductionsupporting
confidence: 86%
“…Furthermore, they used a modeling approach to show that BOLD activation in PRC was modulated by the confusability of objects. Taken together, their results suggest a role for PRC in fine-grained semantic representations of objects (for review see: Clarke and Tyler, 2015). Similarly, research in patient populations has revealed a necessary role for the anterior temporal cortex, and PRC in particular, in naming highly confusable objects (Kivisaari et al, 2012; Wright et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…[8] Recently it has been suggested that the medial perirhinal cortex, the first region of NFT deposition (Braak stage I)[8], is important in object-related semantic knowledge, particularly for “living items” such as animals, and atrophy in this region correlates with category fluency and naming. [15] While longitudinal decline in naming performance was not associated with Braak stage, naming performance was impaired at baseline and final assessment for individuals with Braak III/IV relative to Braak stage I/II. Collectively, these findings along with immediate delayed recall decline implicate a critical role for temporal lobe involvement in the cognitive difficulties observed in individuals meeting neuropathological criteria for PART.…”
Section: Discussionmentioning
confidence: 99%
“…Computational models of semantic cognition propose that concepts are represented by a similarity-based code in an amodal "semantic hub," situated in the apex of the ventral processing stream in the temporal pole (TP) (17,18). Although other regions, such as the temporo-parietal cortex (19), have also been linked to the representation of abstract conceptual knowledge, the TP is most consistently implicated in both patient and neuroimaging studies (17,20,21).These computational models therefore make clear predictions about the expected neural basis of semantic false memory. Namely, the TP semantic hub should contain a similarity-based code, such that the neural representations of DRM words reflect the known semantic relatedness between those words.…”
mentioning
confidence: 99%